Resource Allocation in Bank Supervision: Trade‐Offs and Outcomes - EISENBACH, THOMAS M.; LUCCA, DAVID O.; TOWNSEND, ROBERT M. (Journal of Finance, 2022)
ABSTRACT We estimate a structural model of resource allocation on work hours of Federal Reserve bank supervisors to disentangle how supervisory technology, preferences, and resource constraints impact bank outcomes. We find a significant effect of supervision on bank risk and large technological scale economies with respect to bank size. Consistent with macroprudential objectives, revealed supervisory preferences disproportionately weight larger banks, especially post‐2008 when a resource reallocation to larger banks increased risk on average across all banks. Shadow cost estimates show tight resources around the financial crisis and counterfactuals indicate that binding constraints have large effects on the distribution of bank outcomes.